Listening Comprehension: Some Considerations for Students at the German Department of Hanoi University, Vietnam - Pham, Thi Xuan (Journal of Letters, 2018)
In their third semester, students at the German Department of Hanoi University aim to attain level B2 in listening comprehension. The textbook Aspekte Neu B2 is used for this purpose. However, difficulties arise during the learning process, resulting in students not being able to understand the learning material offered in the classroom. This article addresses two questions: what are the difficulties in listening to a lesson for German as a Foreign Language, and how could a teacher help their learners to overcome these difficulties?